Role of the CCL2-CCR2 axis in cardiovascular disease: Pathogenesis and clinical implications - Zhang, Haixia; Yang, Ke; Chen, Feng; Liu, Qianqian; Ni, Jingyu; Cao, Weilong; Hua, Yunqing; He, Feng; Liu, Zhihao; Li, Lan; Fan, Guanwei (Frontiers in Immunology, 2022)
The CCL2-CCR2 axis is one of the major chemokine signaling pathways that has received special attention because of its function in the development and progression of cardiovascular disease. Numerous investigations have been performed over the past decades to explore the function of the CCL2-CCR2 signaling axis in cardiovascular disease. Laboratory data on the CCL2-CCR2 axis for cardiovascular disease have shown satisfactory outcomes, yet its clinical translation remains challenging. In this article, we describe the mechanisms of action of the CCL2-CCR2 axis in the development and evolution of cardiovascular diseases including heart failure, atherosclerosis and coronary atherosclerotic heart disease, hypertension and myocardial disease. Laboratory and clinical data on the use of the CCL2-CCR2 pathway as a targeted therapy for cardiovascular diseases are summarized. The potential of the CCL2-CCR2 axis in the treatment of cardiovascular diseases is explored.